Capabilities Comparison Of The Augmented Reality Application Development Frameworks On The Android Platform - Suryani, Mifta Aprilya; Jambak, Muhammad Ihsan; Putra, Pacu (AI Society & STMIK Indonesia, 2024)
In the implementation of augmented reality, the natural process of human-computer interaction continues to be a challenge, specifically to reduce the complexity in the effort of using and providing comfortability. Therefore, it is necessary to search for methods and tools to simplify the complex process of building Augmented Reality applications. Vuforia is a multi-platform that has long been used as an Augmented Reality application development framework. Android and iOS platform frameworks are the new alternatives following the development of cellular technology. Furthermore, a comparative capability was conducted between Vuforia and ARCore on the Android platform. The general performance and the ability to understand the environment include working in horizontal and vertical planes, the ability to work based on lighting conditions, and the distance of the camera during the tests. The results showed that ARCore is superior to Vuforia in almost all testing metrics. However, in overexposed or too dim lighting and at very close surfaces, Vuforia is slightly superior but not essential. Therefore, it can be concluded that ARCore's capability is better than Vuforia.